2020
DOI: 10.1111/crj.13291
|View full text |Cite
|
Sign up to set email alerts
|

The combination of pretreatment prognostic nutritional index and neuron‐specific enolase enhances prognosis predicting value of small cell lung cancer

Abstract: Introduction Tumor and immune‐inflammatory biomarkers have been demonstrated to be closely associated with cancer prognosis. Objective The present study aims to assess the prognostic value of pretreatment prognostic nutritional index (PNI), carcinoembryonic antigen (CEA), and neuron‐specific enolase (NSE) in small cell lung cancer (SCLC). Methods A retrospective analysis of 301 SCLC patients treated with platinum‐based chemotherapy was performed. Overall survival (OS) was assessed by Kaplan–Meier and multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Notably, CEA, CA724, CA125, CA199, and AFP are often highly correlated with digestive system tumors and have a weak role in lung cancer. NSE is the preferred marker for detecting SCLC ( 30 , 31 ) and was also found to be weakly associated with NSCLC in this study. Cytokeratin 211 and squamous cell carcinoma antigen are considered the most valuable serum markers for NSCLC.…”
Section: Discussionsupporting
confidence: 53%
“…Notably, CEA, CA724, CA125, CA199, and AFP are often highly correlated with digestive system tumors and have a weak role in lung cancer. NSE is the preferred marker for detecting SCLC ( 30 , 31 ) and was also found to be weakly associated with NSCLC in this study. Cytokeratin 211 and squamous cell carcinoma antigen are considered the most valuable serum markers for NSCLC.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, a study of 301 cases of small cell lung cancer (163 limited-stage cases, 54.2%; 138 extensive-stage cases, 45.8%) found that nutritional status before treatment initiation and NSE level (15 ng/mL) were prognostic factors, in addition to the treatment strategy (localized-stage or extensive-stage chest irradiation). A previous study reported that patients with NSE > 15 ng/mL had a poor prognosis (Wang et al 2021 ). A systematic review of 18 studies and 2981 cases reported that NSE is a predictor of overall survival and progression-free survival (Tian et al 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…In our case, LDH, NSE, and pro-GRP levels in the blood were simultaneously elevated, but these three markers are useful in the diagnosis and prognosis of SCLC. 68 Under microscopy, the tumor cells were small and deeply stained with extrusion deformation, which should be distinguished from some small round cell tumors in the lungs. (1) First, the serological data, microscopic morphology, and immunohistochemical results of neuroendocrine markers easily results in a misdiagnosis of SCLC because it is more common than RMS in the lungs.…”
Section: Discussionmentioning
confidence: 99%